Numerical Complex Analysis Method for Parameters Identification of Anisotropic Media Using Applied Quasipotential Tomographic Data. Part 1: Problem Statement and its Approximation - Bomba, A.Ya.; Boichura, M.V. (Математичне та комп'ютерне моделювання. Серія: Фізико-математичні науки, 2018)
The approach to the solving of gradient problems of parameters identification of quasiideal fields with using applied quasipotential tomographic data based on numerical complex analysis methods is transferred to cases of anisotropic media. We, similar to the existing works of world scientists, some additional information about the nature of the distribution of conductivity inside the domain (research object) is considered a priori known. However, in opposite to the traditional approaches to the statement and solving the problems of electrical impedance tomography, we set the local velocities distribution of a substance (liquid, current) in addition to the averaged potential at the contact sections of plate and body and at other sections (stream lines), we set the potential distribution (according to experimental data, which we approximate using splines, Bezier curves, etc.). Generation of initial data at the boundary of the investigated object is carried out in accordance with the polar model of current injection and a given sum of eigenvalues of the conductivity tensor of the medium. The presence of this kind of data greatly accelerates the process of further solving the problem, which is convenient, in particular, when verifying the method that developed by authors. The corresponding problem is reduced to the iterative solving of a series of problems for the Laplace type equations, where instead of «boundary numerical analogues of the Cauchy-Riemann type equations » appear the ratio of quasiorthogonality with using special types of optimization conditions. In particular: the minimizing functional is constructed by taking into account the Cauchy-Riemann type conditions, the relation between eigenvalues of corresponding anisotropy tensor and also regularizing term; the condition-restriction is built based on ellipticity conditions. Підхід до розв’язання градієнтних задач ідентифікації параметрів квазіідеальних полів за даними томографії прикладених квазіпотенціалів на основі числових методів комплексного аналізу перенесено на випадки анізотропних середовищ. При цьому, аналогічно до існуючих робіт світових вчених, апріорно відомими вважаються деякі додаткові відомості про характер розподілу провідності всередині області (об’єкта дослідження). Проте, на відміну від традиційних підходів до постановки та розв’язання задач електроімпедансної томографії, на ділянках контакту пластинки і тіла окрім усередненого потенціалу тут задається ще й розподіл локальних швидкостей речовини (рідини, струму), а на інших ділянках (лініях течії) — розподіл потенціалу (за експериментальними даними, які апроксимуємо із застосуванням сплайнів, кривих Безьє тощо). Генерація вихідних даних на межі досліджуваного об’єкта здійснюється відповідно до полярної моделі (схеми) інжекції струму при заданій сумі власних значень тензора провідності середовища. Наявність такого виду даних значно пришвидшує процес подальшого розв’язання поставленої задачі, що зручно, зокрема, при верифікації розробленого авторами методу. Відповідна задача зводиться до ітераційного розв’язання серії задач для рівнянь типу Лапласа, де замість «приграничних числових аналогів рівнянь типу Коші-Рімана» фігурують співвідношення квазіортогональності за спеціальних типів умов оптимізації. А саме: мінімізуючий функціонал побудований з урахуванням умов типу Коші-Рімана, співвідношення між відповідними тензору анізотропії власними значеннями, а також регуляризуючого доданку; умови-обмеження сформовані на основі умов еліптичності.